The evolution of the natural rate of interest: Evidence from the Scandinavian countries - Hanna Armelius; Martin Solberger; Erik Spånberg; Pär Österholm (Örebro University School of Business, 2023)
In this paper, the natural rate of interest in Denmark, Norway and Sweden are estimated. This is done by augmenting the Laubach and Williams (2003) framework with a dynamic factor model linked to economic indicators - a modelling choice which allows us to better identify business cycle fluctuations. We estimate the model using Bayesian methods on data ranging from 1990Q1 to 2022Q4. The results indicate that the natural rate has declined substantially and in all countries is at a low level at the end of the sample.
Keywords: E31; E43; E52; 330; Monetary policy; Business cycle; Bayesian filter; Dynamic factor model